PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI, GAYA KEPEMIMPINAN, DAN KOMPETENSI TERHADAP KINERJA PEMERINTAHAN DAERAH (STUDI EMPIRIS PADA KABUPATEN BANGKALAN) - - Mufarrohah; Sutrisno T; Bambang Purnomosidhi (Universitas Trunojoyo Madura, 2013)
This research aims to test and prove empirically the effect of organizational culture, organizational commitment, leadership style, and competence on the local government performance. The data collection in this research is conducted by survey method. Sample of this research is the functionary staffs of echelon II and echelon III in Local Government Bangkalan. Techniques of data analysis employs Structural Equation Modeling (SEM) and analysis tool utilizes Partial Least Square (PLS). The results of this research indicate that there is a positive influence of organizational culture, leadership style, and the competence on the local government performance of Bangkalan. When the organizational culture, leadership style and competence is high, the performance of local government is also high. Organizational commitment has a negative influence and significant on the performance of local government Bangkalan.